2022
DOI: 10.3390/s22020648
|View full text |Cite
|
Sign up to set email alerts
|

Marine Robotics for Deep-Sea Specimen Collection: A Systematic Review of Underwater Grippers

Abstract: The collection of delicate deep-sea specimens of biological interest with remotely operated vehicle (ROV) industrial grippers and tools is a long and expensive procedure. Industrial grippers were originally designed for heavy manipulation tasks, while sampling specimens requires dexterity and precision. We describe the grippers and tools commonly used in underwater sampling for scientific purposes, systematically review the state of the art of research in underwater gripping technologies, and identify design t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…As pointed out in [22], research prototypes of grippers successfully demonstrated cnidarian collection. Dendronephthya and scleractinians were collected with the bellowtype actuator, and an alcyonacean whip coral with the boa-type [29,30]; both grippers implemented a scissor-like cutting tool.…”
Section: Cnidariansmentioning
confidence: 92%
See 4 more Smart Citations
“…As pointed out in [22], research prototypes of grippers successfully demonstrated cnidarian collection. Dendronephthya and scleractinians were collected with the bellowtype actuator, and an alcyonacean whip coral with the boa-type [29,30]; both grippers implemented a scissor-like cutting tool.…”
Section: Cnidariansmentioning
confidence: 92%
“…This process required two steps, the results of which are reported in the present series of two papers. The first step consisted of a thorough analysis of the commercially available gripper technologies currently used for underwater collection of scientific samples, and a systematic review of the research status of underwater grippers, which we performed in [22]. As a second step, in this paper, we investigated the manipulative actions needed in underwater manipulation for the collection of scientific samples.…”
Section: Structure Of the Papermentioning
confidence: 99%
See 3 more Smart Citations